The Clinical Relevance of Hyperkyphosis: A Narrative Review - Koelé, M. C.; Lems, W. F.; Willems, H. C. (Frontiers in Endocrinology, 2020)
The kyphosis angle of the thoracic spine tends to increase with ageing. Hyperkyphosis is a kyphosis angle, exceeding the normal range. This narrative literature review aims to provide an overview of the current literature concerning kyphosis measurement methods, the etiology and adverse health effects of hyperkyphosis. As of yet, a well-defined threshold for hyperkyphosis is lacking. To attain more generalisability and to be able to compare study results in older adults, we propose to define age-related hyperkyphosis as a Cobb angle of 50 degrees or more in standing position. Hyperkyphosis may be a potentially modifiable risk factor for adverse health outcomes, like fall risk and fractures. Additionally, hyperkyphosis may indicate the presence of osteoporosis, which is treatable. Prospective and intervention studies, using a Cobb angle of 50 degrees as a clear and uniform definition of hyperkyphosis, are warranted to investigate the clinical relevance of hyperkyphosis.